Sustainable development and forest-based industries: Main considerations and policy measures : the Bulgarian example - Nikolay Neykov; Petar Antov; Viktor Savov (Open Economics, 2018)
Industrial policy determines the industry's orientation for growth, in line with the economic development stage. The main objective of this article is to establish the sustainability of the relationship between the development of forest resources, on the one hand, and their use in wood and furniture products in the Republic of Bulgaria, on the other hand. The main tasks are to find out the sustainability in the production of timber and products from it, to assess the tendency of development and needs of policy measures. The methods used include statistical methods for trend analysis, descriptive methods and others. Forestry is a clear example of the transformation of natural resources into consumer products, where sustainability in the development of society can easily be disturbed. Forestry policies should support the use of tree resources in products with the highest possible added value.
Keywords: L73; O25; O44; Q23; 330; Forest-based Industries; Sustainable Development; Bulgaria